Pentingnya Kebugaran Jasmani Dalam Pengembangan Keterampilan Motorik Pada Anak Usia Dini: Tinjauan Program Olahraga - Iffatul Awla; Rivan Saghita Pratama (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
Physical Fitness Is An Important Aspect Of Early Childhood Development That Supports Physical, Mental, And Social Health. This Article Discusses The Importance Of Physical Fitness And Various Types Of Sports Programs For Early Childhood. The Main Focus Of This Article Is On The Development Of Children's Motor Skills, Including Gross And Fine Motor Skills, And How Sports Programs Can Be Designed To Improve Both Skills. Through A Literature Review, This Article Evaluates The Effectiveness Of Various Types Of Physical Activities Such As Rhythmic Gymnastics, Running, Swimming, And Ball Games. The Conclusion Of This Study Emphasizes That Well-Designed Sports Programs Not Only Improve Physical Fitness But Also Support The Development Of Children's Motor, Social, And Emotional Skills. Recommendations For The Implementation Of Effective Sports Programs Are Provided Based On The Findings Of The Existing Literature Review.